2013
DOI: 10.2214/ajr.12.10204
|View full text |Cite
|
Sign up to set email alerts
|

Are There Useful CT Features to Differentiate Renal Cell Carcinoma From Lipid-Poor Renal Angiomyolipoma?

Abstract: Specific CT features can potentially be used to differentiate lipid-poor renal angiomyolipoma from renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 34 publications
9
72
0
Order By: Relevance
“…The fp-AMLs were found to have a significantly greater rate of unenhanced attenuation of >38.5 HU and enhanced homogeneity. 17 Still other findings have been associated with fp-AML. Renal masses, which have been described as having either an angular interface with the adjacent parenchyma or having a shape resembling an ''icecream cone'' or ''mushroom, '' 17,23 are more likely to be fp-AML (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The fp-AMLs were found to have a significantly greater rate of unenhanced attenuation of >38.5 HU and enhanced homogeneity. 17 Still other findings have been associated with fp-AML. Renal masses, which have been described as having either an angular interface with the adjacent parenchyma or having a shape resembling an ''icecream cone'' or ''mushroom, '' 17,23 are more likely to be fp-AML (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, no fat can be visualized on CT in approximately 4.5% of AMLs. These tumors are referred to as lp-AMLs [25] . Our data showed that it is very difficult even for an experienced radiologist to diagnose lp-AMLs accurately.…”
Section: Discussionmentioning
confidence: 99%
“…These results imply that tumor attenuation on unenhanced scans may vary, reason why high tumor attenuation on unenhanced scans should not be used as a definitive finding for AML with minimal fat. Yang et al categorized lipid-poor AML based on homogeneity with a homogeneous enhancement pattern for fat poor AML and a heterogeneous enhancement pattern for clear-cell RCC [3] nevertheless the majority of chromophobe RCC and papillary RCC tumors revealed a homogeneous pattern [2,6] . Calcification was also another criteria used to differentiate fat poor AML from RCC in non-contrast CT as intra-tumoral calcification is a common finding in RCCs and may be seen in about 30% of cases [11] , whereas it is rare in AML [5,24] .…”
Section: Iso-attenuating Aml:-mentioning
confidence: 99%
“…AML characteristically expresses melanocytic markers including HMB-45 and Melan-A. The availability of melanocytic markers to diagnose AML produced more precise categorization of tumors of exceptional histology that previously may have been miscategorized [3] . Monophasic AMLs contrast histologically from triphasic AMLs in that they are made of predominantly or completely of 1 component some of which are smooth muscle or fat.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%